2007
DOI: 10.1111/j.1529-8817.2007.00377.x
|View full text |Cite
|
Sign up to set email alerts
|

A COMPARISON OF PHOTORESPONSE AMONG TEN DIFFERENT KARENIA BREVIS (DINOPHYCEAE) ISOLATES1

Abstract: Many laboratories have solely used the Wilson isolate to physiologically characterize the harmful algal bloom (HAB) dinoflagellate Karenia brevis (C. C. Davis) G. Hansen et Moestrup. However, analysis of one isolate may lead to misinterpretations when extrapolating measurements to field populations. In this study, pulse-amplitude-modulated chlorophyll fluorometer (PAM-FL) relative electron transport rate (ETR), F v ⁄ F m , and chl were compared with traditional techniques, such as 14 C photosynthesis versus ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…More recently, however, Schaeffer et al (2007) found variability in the photosynthesis-irradiance response between clones with a wide range of values for the initial slope of the photosynthesis vs. irradiance (P vs. E) curve and the maximum rate of photosynthesis per unit irradiance. They suggest that some clones of K. brevis are not strictly low light adapted and can easily grow at typical surface irradiances.…”
Section: Light Pigments Photosynthesis and Growthmentioning
confidence: 97%
“…More recently, however, Schaeffer et al (2007) found variability in the photosynthesis-irradiance response between clones with a wide range of values for the initial slope of the photosynthesis vs. irradiance (P vs. E) curve and the maximum rate of photosynthesis per unit irradiance. They suggest that some clones of K. brevis are not strictly low light adapted and can easily grow at typical surface irradiances.…”
Section: Light Pigments Photosynthesis and Growthmentioning
confidence: 97%
“…While these data are insufficient to claim the occurrence of a specific type of cell death they certainly provide evidence of the cells' deteriorating condition . 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 (Schaeffer et al, 2007;. However, the maintenance of high F v /F m values even during the decline phase of the cultures is unexpected and surprising since F v /F m is commonly used as an indicator of the physiological state of cells, which responds mostly to nutrient limitation and high irradiance (Kolber and Falkowski, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Results presented here lead to the conclusion that cells follow an optimization scheme based on threshold limits to control vertical migration in the water column. Competition for space and time at the surface may have induced cells to expose themselves to photo-inhibiting light (Schaeffer et al, 2007). However, the average time spent at a photo-inhibiting light location may be insignificant when compared to the reward of obtaining an optimal position for carbon fixation later.…”
Section: H-n-replete H-n-reducedmentioning
confidence: 95%